A novel biocompatible zwitterionic polyurethane with AIE effect for cell imaging in living cells. Issue 13 (12th February 2018) - Xu, Junhuai; Yan, Rui; Wang, Haibo; Du, Zongliang; Gu, Jun; Cheng, Xu; Xiong, Junjie
Abstract : In this work, a novel and stable zwitterionic polymer (TPE-CB PUs) was prepared to realize a cellular imaging system. Abstract : In this work, a novel and stable zwitterionic polymer (TPE-CB PUs) was prepared to realize a cellular imaging system. TPE was conjugated into the backbone of zwitterionic polyurethane, which could be well dispersed in aqueous solution and emitted strong blue fluorescence because the TPE segment was aggregated in the core of TPE-CB PUs micelles. More importantly, the TPE-CB PUs micelles showed significant stability in a large pH window and with different storage times. In addition, the micelles exhibited low cytotoxicity in HeLa cells and mainly distributed in the cytoplasm after being incubated with cells. The outstanding properties of TPE-CB PUs combining the merits of AIE and a zwitterionic segment highlight its potential for use as a cell imaging material with remarkable capability.